Experimental and numerical investigation on premixed H2/air combustion. (29th June 2016) - Liu, Yinhe; Zhang, Yun; Liu, Xiaoqian; Liu, Ziyu; Che, Defu
Abstract: Experimental investigation and numerical simulation are performed to obtain the combustion characteristics of premixed hydrogen/air mixtures in a closed container, such as flame propagation velocity, peak pressure and maximum temperature. This paper mainly focused on the influence of initial temperature, hydrogen concentration and steam concentration on hydrogen/air flame propagation. An updated kinetics of hydrogen combustion based on one-step global reaction mechanism was validated by the present experimental data. The numerical results with updated kinetics show a satisfactory agreement with experimental results in term of average flame propagation velocity with the deviation less than 20%. The experimental and simulation results show that the average flame propagation velocity increases with the increase of initial hydrogen concentration and initial temperature, and reduces with the increase of initial steam concentration. The effect of hydrogen concentration on average flame propagation velocity is more significant than that of initial temperature and steam concentration. Highlights: The combustion of premixed hydrogen/air in a closed container is studied. Initial hydrogen concentration plays a significant role on flame propagation. An updated kinetics of H2 /air combustion is validated by present experiments. Initial temperature and concentration influence the consumed hydrogen ratio.